PENJADWALAN DISTRIBUSI SEMEN KANTONG DI UNIT TERMINAL PENGANTONGAN SEMEN PT LAPLACE CEMENT INDONESIA LHOKNGA BANDA ACEH - Mahdi Mahdi (Jurnal Optimalisasi, 2015)
PT. Lafarge Cement Indonesia (LCI) Lhoknga, have produced their products to reach 1.78 million tons per year onwards. PT. Lafarge Cement Andalas (LCI) Indonesia Lhoknga has port facilities themselves in Lhoknga, also some bag terminal contained in Lhokseumawe, Belawan, Batam, and On the distribution of bagged cement in Lhoknga packing stasiun is not maximized because of the overall quota provided only 60% per month which taken by the distributor of the sales target. Distribution scheduling methods do by using Visual Basic 2010 facilitated program Semen RF Ugha 68. An initial simulation results can be used to analyze the amount of the distribution and the distribution shifts per day with a certain amount of quota that is not the same each month or per day depending on the number of working days will be used. In the program Ugha Cement RF 68 just counting the number of quota per month, per day, the amount of the effective time, the number of maneuvers the truck, and the number of bags per day to be distributed. The final results of how the amount of the actual time required to distribute the total quota Based on the results waiting time machine the bag terminal caused by several things including, the quota system, scheduling less well planned, distributors do not consistently take the cement appropriate amount of quota per day that has been allocated, and the determination of the day working up to 30 working days to reach the number of hours worked two shifts.Keywords: PT. Lafarge Cement Indonesia, distribution scheduling, Visual Basic 2010, ugha Cement RF 68.